2021
DOI: 10.1088/1361-648x/ac3fd8
|View full text |Cite
|
Sign up to set email alerts
|

Extended law of corresponding states: square-well oblates

Abstract: The vapour-liquid coexistence collapse in the reduced temperature, Tr=T/Tc, reduced density, ρr= ρ/ρc, plane is known as a principle of corresponding states, and Noro and Frenkel have extended it for pair potentials of variable range. Here, we provide a theoretical basis supporting this extension and show that it can also be applied to short-range pair potentials where both repulsive and attractive parts can be anisotropic. We observe that the binodals of oblate hard ellipsoids for a given aspect ratio (κ=1/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 61 publications
(83 reference statements)
0
5
0
Order By: Relevance
“…In Figure , the binodals for COE-01 under low ionic strength conditions and for COE-07 under salting-out conditions are plotted in terms of Δ b 22 = b 22 – b 22 c and compared against experimental data for lysozyme and results obtained from molecular simulations of square-well fluids for two different ranges given by λ = 1.1, 1.25, where λ is the range of the square well normalized by the hard sphere diameter. It has been shown that an extended law of corresponding states is applicable when the binodal is plotted in terns of Δ b 22 for nonspherical convex particles interacting through isotropic and weakly anisotropic interactions. , For lysozyme the dilute branch is captured by both models, but the dense branch is better fit to the shorter-ranged potential as the binodal is thinner for λ > 1.25. While the behavior of lysozyme agrees reasonably well with the phase diagrams of model potentials, the binodals of the mAbs deviate greatly from the behavior.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In Figure , the binodals for COE-01 under low ionic strength conditions and for COE-07 under salting-out conditions are plotted in terms of Δ b 22 = b 22 – b 22 c and compared against experimental data for lysozyme and results obtained from molecular simulations of square-well fluids for two different ranges given by λ = 1.1, 1.25, where λ is the range of the square well normalized by the hard sphere diameter. It has been shown that an extended law of corresponding states is applicable when the binodal is plotted in terns of Δ b 22 for nonspherical convex particles interacting through isotropic and weakly anisotropic interactions. , For lysozyme the dilute branch is captured by both models, but the dense branch is better fit to the shorter-ranged potential as the binodal is thinner for λ > 1.25. While the behavior of lysozyme agrees reasonably well with the phase diagrams of model potentials, the binodals of the mAbs deviate greatly from the behavior.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that an extended law of corresponding states is applicable when the binodal is plotted in terns of Δb 22 for nonspherical convex particles interacting through isotropic and weakly anisotropic interactions. 65,66 For lysozyme the dilute branch is captured by both models, but the dense branch is better fit to the shorter-ranged potential as the binodal is thinner for λ > 1.25. While the behavior of lysozyme agrees reasonably well with the phase diagrams of model potentials, the binodals of the mAbs deviate greatly from the behavior.…”
Section: Measurement Of Protein−protein Interactions Inmentioning
confidence: 99%
See 2 more Smart Citations
“…The first contribution of this section is written by de Santiago et al [13] and shows that the extended law of corresponding states of Noro and Frenkel, originally developed for pair potentials of variable range, can also be applied to short-range pair potentials with both attractive and repulsive anisotropic interactions. As an illustrative example the authors considered oblate hard ellipsoids with varying short-range square-well interactions using perturbation theory and simulations.…”
Section: Interaction Potentials In Soft Mattermentioning
confidence: 99%